1993
DOI: 10.1172/jci116920
|View full text |Cite
|
Sign up to set email alerts
|

Bence Jones proteins bind to a common peptide segment of Tamm-Horsfall glycoprotein to promote heterotypic aggregation.

Abstract: Bence Jones proteins (BJPs) are the major pathogenic factor causing cast nephropathy ("myeloma kidney") by coaggregation with Tamm-Horsfall glycoprotein (THP). Understanding the interaction between these proteins is therefore important in developing treatment strategies to prevent renal failure from cast formation in multiple myeloma. We developed an enzymelinked immunoassay to examine this phenomenon. Five different human BJPs (four K and one X immunoglobulin light chains) were used in this assay that demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 28 publications
5
43
0
1
Order By: Relevance
“…A fourth isoform that contains a 22-residue deletion within the second calcium-binding EGF-like domain has also been suggested. Prior studies identified a single FLC-binding domain (LCBD) on THP where FLCs bind (14,15). The LCBD of THP was within the D8C region just downstream of the last residue absent from isoform no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fourth isoform that contains a 22-residue deletion within the second calcium-binding EGF-like domain has also been suggested. Prior studies identified a single FLC-binding domain (LCBD) on THP where FLCs bind (14,15). The LCBD of THP was within the D8C region just downstream of the last residue absent from isoform no.…”
Section: Discussionmentioning
confidence: 99%
“…Human THP and FLCs were purified from urine in standard fashion (6,7,(14)(15)(16)30). Purified human THP was biotinylated as described previously (36), using sulfo-N-hydroxysuccinimide biotin (ImmunoPure Sulfo-NHS-Biotin; Pierce Protein Products, Thermo Fisher Scientific), followed by dialysis against PBS at 4°C for 24 hours to remove free biotin.…”
Section: Reagents Qsydntlsgsyvf Cqsydntlsgsyvfc Ahx-lsadssgsy-mentioning
confidence: 99%
“…Abnormal deposition of THP and ensuing inflammatory reactions have been consistently observed in cast nephropathy and urolithiasis (13,16). In acute renal transplant rejection THP deposits were found to be surrounded by mononuclear cell infiltrates (42), similar to kidneys affected by immunoglobulin light chain deposition in patients with multiple myeloma (43). Despite the apparent participation of THP in a large variety of inflammatory kidney diseases, the underlying mechanisms that would explain how THP contributes to inflammatory reactions have largely remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Cast nephropathy, or "myeloma kidney," is a common complication of multiple myeloma. Binding and subsequent coaggregation of filtered immunoglobulin light chains (LCs) with THP obstruct flow through the renal tubule and result in renal failure (6,7). Both and LCs share a common binding site on THP, although different nephrotoxic LCs possess different affinities for THP (6).…”
Section: Introductionmentioning
confidence: 99%